The urban question and participation in the decision-making process - Serra, Geraldo G. (Revista do Instituto de Estudos Brasileiros, 1994)
Representation and participation of citizens in decisions of urban questions, principally those relating to the allocation of scarce resources, including even the allocation of urban planning and administration. Centralization and decentralization. Spacial compartmentalization as a way of generating participation of citizens. Forms of participation. Participation and technocracy. The limits of the process of the participation of the citizens in the urban sphere.